ETIOLOGICAL STRUCTURE OF CHRONIC OSTEOMYELITIS IN PATIENTS AND THE EFFECTIVENESS OF ANTIBIOTIC THERAPY - Fotima Sh. Mamatmusaeva; Zulfiya B. Djuraeva; Dilnoza F. Raimkulova; Botir S. Ermatov (Central Asian Journal of Medicine, 2024)
Purpose of the study. To study the main causative agents of chronic osteomyelitis and their sensitivity to antibiotics. Materials and methods. The composition of purulent discharge was studied in 41 patients with chronic osteomyelitis aged 18-70 years who were treated in the Department of Purulent Surgery of the Multidisciplinary Clinic of the Tashkent Medical Academy. Analysis and discussion of results. 41 patients with chronic osteomyelitis were selected for screening. All these patients underwent bacteriological examination. Conclusion. According to the results of our study on antibiotic resistance, it is necessary to identify microorganisms and conduct an antibiogram. In the course of our studies, according to the results of a bacteriological study, it was found that the drugs of choice in treatment are levofloxacin, augmatini, tetracycline, sefaperazon.